2008
DOI: 10.7326/0003-4819-148-11-200806030-00009
|View full text |Cite
|
Sign up to set email alerts
|

Performance during Internal Medicine Residency Training and Subsequent Disciplinary Action by State Licensing Boards

Abstract: Poor performance on behavioral and cognitive measures during residency are associated with greater risk for state licensing board actions against practicing physicians at every point on a performance continuum. These findings support the Accreditation Council for Graduate Medical Education standards for professionalism and cognitive performance and the development of best practices to remediate these deficiencies.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
161
0
3

Year Published

2010
2010
2024
2024

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 218 publications
(166 citation statements)
references
References 32 publications
2
161
0
3
Order By: Relevance
“…Papadakis et al then reviewed state licensing board disciplinary actions against 66,171 physicians who entered United States internal medicine residency training programs from 1990 to 2000 to determine whether behaviour during residency also predicted the likelihood of future disciplinary actions against practicing physicians. 7 A low professionalism rating on the resident's annual in-training evaluation summary predicted an increased risk for disciplinary action, and a high performance on the American Board of Internal Medicine certification examination predicted a decreased risk for disciplinary action.…”
Section: Predicting Problem Patterns Of Behaviour In Physiciansmentioning
confidence: 99%
“…Papadakis et al then reviewed state licensing board disciplinary actions against 66,171 physicians who entered United States internal medicine residency training programs from 1990 to 2000 to determine whether behaviour during residency also predicted the likelihood of future disciplinary actions against practicing physicians. 7 A low professionalism rating on the resident's annual in-training evaluation summary predicted an increased risk for disciplinary action, and a high performance on the American Board of Internal Medicine certification examination predicted a decreased risk for disciplinary action.…”
Section: Predicting Problem Patterns Of Behaviour In Physiciansmentioning
confidence: 99%
“…Ratings on the RAES have been shown to correlate with performance on the certifying examination, peer ratings of postlicensure performance, and professional behavior in practice. [18][19][20] A descriptive analysis compared the professionalism ratings with the 2 ratings procedures. Residents with low scores in professionalism were identified as those rated as unsatisfactory (<4) in professionalism on the RAES form, 20 or those rated below a 2.5 and below a 2 on any of the 4 professionalism subcompetencies of the milestones.…”
Section: Statistical Analysesmentioning
confidence: 99%
“…In a review article, van Mook et al (2014) examines the multiple issues related to the identification and remediation of ''dyscompetent'' residents, particularly in the area of professionalism. And an original study by Santen et al (2014) extends the findings of two landmark studies by Papadakis et al (2004Papadakis et al ( , 2008, which showed that unprofessional behavior in practice was apparently predictable from performance in medical school. Both studies used a ''case control'' design in which individuals who had the outcome of interest (discipline by a state licensing body)-''cases'' were compared to a random sample of doctors who were not reported-''controls''.…”
mentioning
confidence: 74%